PARP-1 Controls the Adipogenic Transcriptional Program by PARylating C/EBPβ and Modulating Its Transcriptional Activity - Luo, Xin (Mol Cell, 2017)
Poly(ADP-ribosyl)ation (PARylation) is a post-translational modification of proteins mediated by PARP family members, such as PARP-1. Although PARylation has been studied extensively, few examples of definitive biological roles for site-specific PARylation have been reported. Here we show that C/EBPβ, a key pro-adipogenic transcription factor, is PARylated by PARP-1 on three amino acids in a conserved regulatory domain. PARylation at these sites inhibits C/EBPβ’s DNA binding and transcriptional activities, and attenuates adipogenesis in various genetic and cell-based models. Interestingly, PARP-1 catalytic activity drops precipitously during the first 48 hours of differentiation, corresponding to a release of C/EBPβ from PARylation-mediated inhibition. This promotes the binding of C/EBPβ at enhancers controlling the expression of adipogenic target genes and continued differentiation. Depletion or chemical inhibition of PARP-1, or mutation of the PARylation sites on C/EBPβ, enhances these early adipogenic events. Collectively, our results provide a clear example of how site-specific PARylation drives biological outcomes.